(untitled) (The Indian Journal of Animal Reproduction, 2023)
The inauguration of 38th Annual Convention of ‘The Indian Society for Study of Animal Reproduction’ (ISSAR) and International Symposium on ‘Frontiers in Theriogenology: Research and Practice’ was held on 6th December 2023 at 10 AM in the Golden Jubilee auditorium, College of Veterinary and Animal Sciences, Mannuthy, Thrissur, Kerala. The Chairman of the organizing committee, ISSAR 2023 and Faculty Dean, CVAS, Mannuthy, Prof. (Dr.) K. Vijayakumar welcomed the gathering. The programme was presided over by Prof. (Dr.) Shiv Prasad, President, ISSAR and Prof. (Dr.) M. Selvaraju, Gen. Secretary, ISSAR presented the annual report. The symposium was inaugurated by the chief guest Prof. (Dr.) Mohanan Kunnummal, Hon’ble Vice- Chancellor, Kerala University of Health Sciences. The guest of honour, Prof. (Dr.) M.R. Saseendranath, Hon’ble Vice- Chancellor of Kerala Veterinary and Animal Sciences University addressed the august gathering and released the compendium. The former senior faculty members of the Department of Animal Reproduction, Gynaecology and Obstetrics, Kerala were honoured during the occasion. Felicitations were offered by Prof. (Dr.) T.S. Rajeev, Director of Entrepreneurship, KVASU and Dr. R. Rajeev, Managing Director, Kerala Livestock Development Board. Dr. C. Jayakumar, Organizing Secretary, ISSAR 2023 & Associate Professor and Head, Department of ARGO, CVAS, Mannuthy offered vote of thanks. Dr. Brig. N. M. Singhvi VSM and Dr. Sudhir Kumar Agarwal have been awarded with Life Time Achievement Award 2022 and 2023 respectively. Dr. G. N. Purohit, Dr. Pankaj Sood,